Fast Charging of Energy-Dense Lithium Metal Batteries in Localized Ether-Based Highly Concentrated Electrolytes. Issue 6 (24th June 2021) - Leng, Yongjun; Ge, Shanhai; Yang, Xiao-Guang; Longchamps, Ryan S.; Liu, Teng; Wang, Chao-Yang
Abstract : Li metal batteries (LMBs) employing high voltage cathodes show promise as next generation batteries for electric vehicles due to their high energy density. However, the cycling stability of such energy-dense LMBs at high charge rates has seldom been explored. In this work, Li Coulombic efficiency (CE) as a function of current density (i.e., C-rate) and temperature was investigated in ether-based highly concentrated electrolytes (HCEs). We found that Li metal anodes can be stably cycled in the HCEs at elevated temperatures with a high Li CE of >99.4% for a plating capacity of 3 mAh cm −2 at a high C-rate greater than 1 C. The cycling stability of LMB full cells with Li(Ni0.8 Co0.1 Mn0.1 )O2 (NMC811) cathodes was also investigated at different charge rates (1 C to 3 C) at 40 and 60 °C. The LMBs with high areal capacity (∼3.2 mAh cm −2 ) NMC811 cathodes and minimal Li excess anodes (negative/positive capacity ratio (N/P ratio) <3.1) can achieve ∼189 stable cycles with an average efficiency of ∼99.86% at 1 C charge and C/3 discharge at 60 °C.